2015
DOI: 10.1590/s0100-736x2015000300008
|View full text |Cite
|
Sign up to set email alerts
|

Tipagem molecular e resistência aos antimicrobianos em isolados de Escherichia coli de frangos de corte e de tratadores na Região Metropolitana de Curitiba, Paraná

Abstract: Este estudo verificou o perfil de resistência aos antimicrobianos entre isolados de Escherichia coli de frangos de corte de criação intensiva e de subsistência e dos respectivos tratadores e a similaridade genotípica entre isolados de E.coli de frangos de corte de criação intensiva e isolados de E. coli de tratadores de frangos de criação intensiva pela técnica de Eletroforese em Gel de Campo Pulsado (PFGE). 60 amostras de fezes de frangos de criação intensiva, 60 de frangos de corte de criação de subsistência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(26 reference statements)
1
4
1
2
Order By: Relevance
“…The use of tetracyclines, quinolones and penicillins as feed additives or growth promoters in broiler chickens is prohibited in Brazil [6], however this study found high resistance rates to drugs from these groups (tetracycline, ciprofloxacin and ampicillin). Similar findings were recently found in E. coli samples from feces of broiler chickens reared in intensive system in the Metropolitan Region of Curitiba with the following rates, respectively 83%, 23% and 100% [19]. A previous study [28] revealed lower resistance rates to tetracycline (48%) and ampicillin (42%) when compared to this study, while another study showed higher values in E. coli samples, which 67% were resistant to tetracycline and 84.6% were resistant to ampicillin [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The use of tetracyclines, quinolones and penicillins as feed additives or growth promoters in broiler chickens is prohibited in Brazil [6], however this study found high resistance rates to drugs from these groups (tetracycline, ciprofloxacin and ampicillin). Similar findings were recently found in E. coli samples from feces of broiler chickens reared in intensive system in the Metropolitan Region of Curitiba with the following rates, respectively 83%, 23% and 100% [19]. A previous study [28] revealed lower resistance rates to tetracycline (48%) and ampicillin (42%) when compared to this study, while another study showed higher values in E. coli samples, which 67% were resistant to tetracycline and 84.6% were resistant to ampicillin [34].…”
Section: Discussionsupporting
confidence: 88%
“…However, a study performed in Pernambuco State with 16 E. coli from cecal content of healthy broiler chickens revealed a low resistance rate to trimethoprim-sulfamethoxazole (43.7%) when compared to the present study, while 13 birds that presented clinical signs of respiratory disease revealed a high resistance rate (84.6%) [3]. In addition, recent studies verified elevated resistance in 25 E. coli isolates from cloacal swab samples of healthy broiler chickens to the same antibiotic (84%) [2], unlike what was observed with 60 feces samples of intensive reared broiler chickens, which revealed 45% of resistance to trimethoprim-sulfamethoxazole [19].…”
Section: Discussioncontrasting
confidence: 54%
“…Tetracycline resistance level of the E. coli strains studied was lower than that described in other regions of Brazil [34, 39] and in other countries, such as China, where resistance to tetracycline can reach about 90 % [41]. For many years, tetracycline was used as prevention and as growth promoter in poultry, but the use of antibiotics with these purposes was banned since 2009 in Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…As amostras de Escherichia coli apresentaram 90% (18/20), 50% (10/20), 45% (9/20), 50% (10/20) e 70% (14/20) de resistência à ampicilina, ciprofloxacina, neomicina, sulfonamida e ácido nalidíxico, respectivamente. Resultados semelhantes foram observados por Korb et al (2015) ao analisarem a resistência antimicrobiana a Escherichia coli de origem aviária.…”
Section: Resultsunclassified
“…De acordo com Donini (2018), os Centros para Controle e Prevenção de Doenças (CDC), vinculados ao Departamento de Saúde dos Estados Unidos, estimam que uma em cada cinco infecções resistentes são causadas por microrganismos oriundos de alimentos e animais, o que causa grande preocupação à saúde pública. Por esse motivo, a Organização Mundial de Saúde recomenda o uso prudente dos antimicrobianos na saúde humana e na produção animal (KORB et al, 2015). Esta recomendação procede em virtude de registros de mortes humanas por infecções causadas por bactérias multirresistentes e da dificuldade de introdução de novos antibióticos no mercado.…”
Section: Resultsunclassified